2009
DOI: 10.1002/adma.200800253
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Perovskite‐Fluorite Oblique Nanostructures for Adaptive (Tunable) Electronics

Abstract: Capacitors are essential building blocks of electrical radiofrequency (rf) circuits. Reconfigurable circuits whose electrical characteristics can be altered dynamically are of interest for space and weight economy, especially in future multifunctional, multiband hand-held electronic devices. Electrically tunable capacitors, that is, varactors, are therefore in demand. Two emerging solutions compete over this market: rf-microelectromechanical systems (rf-MEMS) tunable capacitor technology and ferroelectric thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The mechanism of the inclined growth is discussed in Ref. [7]. Figure 4a shows the relationship between volume fraction and nominal molar fraction of CeO 2 in our BaTiO 3 -CeO 2 films on Pt(111).…”
Section: Solubility and Self-assembled Composite Growth Of Batio 3 -Cmentioning
confidence: 93%
See 2 more Smart Citations
“…The mechanism of the inclined growth is discussed in Ref. [7]. Figure 4a shows the relationship between volume fraction and nominal molar fraction of CeO 2 in our BaTiO 3 -CeO 2 films on Pt(111).…”
Section: Solubility and Self-assembled Composite Growth Of Batio 3 -Cmentioning
confidence: 93%
“…Self-assembly techniques are therefore attractive. Recently, we found that, by using BaTiO 3 (i.e., BST x=1) as a ferroelectric and CeO 2 as a low-K dielectric, it is possible to self-assembly grow the oriented composite film structures [7]. In this paper, we report on the details and other features of the growth and dielectric properties of those BaTiO 3 -CeO 2 films.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…4 Finerscale thin-film composites that have a higher percentage of interfaces are more appealing for adaptive tunable electronics. 5 In these and other examples, vital properties of materials for advanced technological applications are strongly influenced or even controlled by the existence of interfaces. To optimize materials for these and other applications, it is critical to understand the role the interfaces play in modifying defect behavior within the material.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of reconfigurable microelectronics, perovskite-fluorite (BaTiO 3 -CeO 2 ) nanocomposites are pivotal as two structurally different immiscible phases, one a ferroelectric and the other a low-permittivity dielectric, are needed for such applications. 5 For use as an effective threeway catalyst in automotive applications 6,7 and high temperature superconductor applications, 8 CeO 2 is often grown on SrTiO 3 (STO) substrates. On the other hand, CeO 2 can also serve as a buffer layer for epitaxial deposition of STO to study ferroelectric properties of STO.…”
Section: Introductionmentioning
confidence: 99%